2019
DOI: 10.1080/14658011.2019.1585099
|View full text |Cite
|
Sign up to set email alerts
|

The influence of zirconia fibre on ablative composite materials

Abstract: Zirconia fibres have excellent high temperature ablation resistance and have been widely used in ablative materials. In this paper, zirconia fibre was used for reinforcing the ablative composite materials to study the influence of zirconia fibre had upon the mechanical properties and the high temperature ablation properties of such composites. The results showed that the bending strength of the material was also good and reached a maximum of 13.05 MPa. After sintering at 1400°C, the bending strength was also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…An ablative composite material was used with zirconia fibers due to its significant mechanical properties and resistance to high-temperature ablation. It revealed that with 30% of zirconium fiber content composite material showed 19.33 MPa of bending strength; also at the higher temperature over 1400 °C, due to eutectic melting reaction, a ceramic protective layer forms which offers bending strength of 13.05 MPa [235].…”
Section: Applicationsmentioning
confidence: 99%
“…An ablative composite material was used with zirconia fibers due to its significant mechanical properties and resistance to high-temperature ablation. It revealed that with 30% of zirconium fiber content composite material showed 19.33 MPa of bending strength; also at the higher temperature over 1400 °C, due to eutectic melting reaction, a ceramic protective layer forms which offers bending strength of 13.05 MPa [235].…”
Section: Applicationsmentioning
confidence: 99%
“…Depending on the hyperthermal environment in which these materials must work, many types of formulations have been developed. Up to now, a wide range of fibers, , powdered fillers, and nanosized reinforcements have been added to the neat matrix to improve the ablation and oxidation resistance of these materials. In most cases, attention was focused on the influence of specific fillers on the ablation performance of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon/Carbon (C/C) ablative materials are well known non-charring ablators which are often employed in the nozzles of rockets [13]. Charring ablative materials consist of an organic resin and one or more reinforcement phases and they guarantee an efficient heat removal thanks to several mechanisms: for phenolic resins, when temperature reaches about 300 °C, the endothermic pyrolysis reaction takes place guaranteeing energy absorption [14][15][16][17]; pyrolysis gasses are produced during the reaction and they absorb part of the heat by warming up themselves and, because of a pressure gradient, they flow in the boundary layer forming a barrier against convective heat exchange, this phenomenon is called blockage effect [2,[18][19][20]]. An ablative thermal protection system needs to satisfy different requirements: i) it has to protect the structure of the reentry vehicle and the payload from overheating; ii) the total required mass need to be as low as possible; iii) the recession of the shield has to be controlled in order to have predictable variations of the mass and shape of the vehicle [21].…”
Section: Introductionmentioning
confidence: 99%